Identification and evaluation of antivirals for Rift Valley fever virus - Lang, Yuekun (Kansas State University, 2017)
Rift Valley fever virus (RVFV) is an enveloped, negative-sense, ssRNA virus with a tripartite genome that causes morbidity and mortality in both livestock and humans. Although RVFV is mainly circulating in mainland Africa, this arthropod-borne virus is a potential threat to the other parts of the world. No fully licensed vaccines for human or animal use in the U.S., and effective antiviral drugs have not been identified. As virulent RVFV strains are only handled in biosafety level (BSL) 3 or higher level facilities in the U.S., few laboratories have access to RVFV which limits antiviral development. However, it is crucial to develop effective antivirals to protect public and animal health. Animal models that reproduce Rift Valley fever are vital to identifying and developing antiviral compounds. The currently available attenuated RVFV strain, MP12, provides a BSL-2 challenge model virus for preliminary investigations of RVFV prior to using the virulent RVFV strains. All strains of RVFV have a highly conserved genome, indicating that antivirals or vaccines effective against any RVFV strain will most likely be effective for all RVFV strains. Therefore, we hypothesize that the MP12 is a suitable model virus that can be used for identification and evaluation of effective RVF antivirals. The first objective of this project was to establish a mouse model susceptible to MP12 infection. Based on the literature, we selected and screened six different strains of mice to test their susceptibilities to MP12. We found the STAT-1 knockout mice are the most susceptible to MP12 infection based on clinical symptoms, mortality, viremia, virus replication, histopathological, and immunochemical analyses. Importantly, these mice displayed acute-onset hepatitis and delayed-onset encephalitis similar to severe cases of human RVFV infection. Our second objective was to identify potential antiviral drugs in vitro. We developed and employed a cell-based assay using the recombinant MP12 virus expressing Renilla luciferase to screen a library of 727 small compounds purchased from National Institutes of Health. Of the compounds, 23 were identified and further tested for their inhibitory activities on the recombinant MP12 virus expressing green fluorescent protein. Further plaque reduction assays confirmed that two compounds inhibited replication of parental RVFV MP12 strain with limited cytotoxic effects. The 50% inhibitory concentrations using an MP12 multiplicity of infection (MOI) of 2 were 211.4 µM and 139.5 µM, respectively. Our third objective was to evaluate these two candidates, 6-azauridine and mitoxantrone, in vivo using our mouse model. After one-hour post MP12 infection via an intranasal route, treatment was given intranasally twice daily. Mice treated with placebo and 6-azauridine displayed severe weight loss and reached the threshold for euthanasia with obvious neurological signs, while mice treated with ribavirin (a known antiviral drug) or mitoxantrone showed delayed onset of disease. This result indicates that the mitoxantrone can improve the outcome of RVFV infection in our mouse model. The underlying mechanism of mitoxantrone to inhibit RVFV replication remains to be investigated. Our studies build the foundation for identification and development of antivirals against RVFV in a BSL-2 environment.
Keywords: Rift Valley fever virus; Antiviral; Mouse model